2006
DOI: 10.1037/0022-0663.98.4.766
|View full text |Cite
|
Sign up to set email alerts
|

Mastery and performance goals predict epistemic and relational conflict regulation.

Abstract: The present research examines whether mastery and performance goals predict different ways of reacting to a sociocognitive conflict with another person over materials to be learned, an issue not yet addressed by the achievement goal literature. Results from 2 studies showed that mastery goals predicted epistemic conflict regulation (a conflict regulation strategy focused on the attempt to integrate both points of view), whereas performance goals predicted relational conflict regulation (a conflict regulation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 77 publications
6
87
0
13
Order By: Relevance
“…Indeed, previous studies indicate that performance goals are working less constructive in social situations than mastery goals (e.g., Darnon et al 2006). The current study goes one step further by showing that performance goals, relative to mastery goals, may not only lead to behavior that is less constructive, but may actually instigate behavior that is targeted at harming the performance of others in the same achievement situation.…”
Section: Toward a Social Understanding Of Achievement Goalsmentioning
confidence: 66%
See 1 more Smart Citation
“…Indeed, previous studies indicate that performance goals are working less constructive in social situations than mastery goals (e.g., Darnon et al 2006). The current study goes one step further by showing that performance goals, relative to mastery goals, may not only lead to behavior that is less constructive, but may actually instigate behavior that is targeted at harming the performance of others in the same achievement situation.…”
Section: Toward a Social Understanding Of Achievement Goalsmentioning
confidence: 66%
“…Darnon et al found that when students have different task-related solutions, performance goals predict relational conflict regulation, that is, by insisting that one is right and the other party is wrong. On the other hand, mastery goals predict epistemic regulation, which means that one tries to find out whether both points of view can be integrated into a joint solution (Darnon et al 2006). A different line of research in the educational domain consistently shows that mastery goals lead to decreased levels of academic cheating, whereas performance goals are related to increases in academic dishonesty (for a review see Murdock and Anderman 2006).…”
Section: Toward a Social Understanding Of Achievement Goalsmentioning
confidence: 99%
“…They usually are not oriented towards cooperation and seek less help and support from others 18) . Because of their "aversion" to sharing and collaboration, they tend more often to demonstrate superiority than to work towards integration of competing values and interests 19) . A performance orientation leads to higher levels of interpersonal conflict with peers and supervisors and to less exchange of knowledge on the work floor 13) , because peers and supervisors are perceived as a threat rather than as a safe source of knowledge and experience.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…L'intérêt pour la dimension opératoire de la prise de décision a fait oublier l'existence de la dimension socio-motivationnelle qui renvoie aux membres du groupe, à leurs relations, à leurs buts et à leurs motivations. Or, ce qui se passe dans un groupe, les résultats auxquels il arrive, dérivent de la combinaison des deux sortes de phénomènes, ceux centrés sur la tâche et ceux relatifs aux membres (Darnon, Muller, Schrager, Pannuzzo, & Butera, 2006). Certes, la coopération paraît être le type de fonctionnement le mieux adapté à des tâches caractérisées par l'interdépendance des ressources comme le sont les « profils cachés ».…”
Section: Approche Motivationnelle De La Prise De Décision En Groupeunclassified